(untitled) (Modern education and development, 2025)
This study investigates the growing influence of ChatGPT and similar artificial intelligence (AI) tools in the educational sector. With the increasing integration of AI in classrooms, online learning platforms, and academic research, this paper evaluates both the benefits and potential challenges associated with these technologies. Findings suggest that while AI enhances personalization, feedback, and access to knowledge, it also raises concerns regarding academic integrity and overreliance.